Climatic, environmental changes and human impacts in Central Africa over the last 10 ka inferred from organic biomarkers - (:unkn) unknown (My University, 2023)
Since the beginning of the Holocene, the African climate has undergone extensive paleoclimatic and paleoenvironmental changes. From a globally humid climate at the beginning of the Holocene known as the African Humid Period (AHP), the climate has become drier since the end of the AHP at around 6 to 4 ka. This recent drier climate is not conducive to the deposition and preservation of sediments, leading to sparse and often discontinuous records that complicate paleoclimatic and paleoenvironmental interpretations based on these archives. This study focuses on a continuous peat core from the NGaoundaba peat deposit (north-east Cameroon) covering the last 10,000 years, using a wide panel of lipid biomarkers with varied biological origins: microbial isoprenoid and branched glycerol tetraethers (isoGDGTs and brGDGTs respectively), plant n-alkanes and degradation products, bacterial hopanoids, ... Using variations in abundance, concentration, isotopic composition or recent empirical calibrations developed for peat, we reconstruct changes in vegetation, precipitation, temperature or methane cycle to better understand the timing and specificities of the African wet period both locally and regionally by comparing to other available records. From 10 to 6 ka, temperatures based on GDGTs, δDC31 n-alc and δ13Cn-alc indicate a warmer, wetter period than the current one, as well as a predominance of C3 plants coinciding with the AHP. Two drier events are visible δDC31 n-alc resulting in numerous changes in vegetation and microbial communities developing in the bog at these times.
Keywords: African Research